Tracking Staphylococcus aureus in the intensive care unit using whole-genome sequencing. Issue 1 (September 2019) - Dancer, S.J.; Adams, C.E.; Smith, J.; Pichon, B.; Kearns, A.; Morrison, D.
Summary: Background: Staphylococcus aureus remains an important bacterial pathogen worldwide. This study utilized known staphylococcal epidemiology to track S. aureus between different ecological reservoirs in one 10-bed intensive care unit (ICU). Methods: Selected hand-touch surfaces, staff hands and air were screened systematically 10 times during 10 months, with patients screened throughout the study. S. aureus isolates were subjected to spa typing and epidemiological analyses, followed by whole-genome sequencing to provide single nucleotide polymorphism (SNP) data. Results: Multiple transmission pathways between patients and reservoirs were investigated. There were 34 transmission events, of which 29 were highly related (<25 SNPs) and five were possibly related (<50 SNPs). Twenty (59%) transmission events occurred between colonized patients and their own body sites (i.e. autogenous spread); four (12%) were associated with cross-transmission between patients; four (12%) occurred between patients and hand-touch sites (bedrails and intravenous pump); four (12%) linked airborne S. aureus with staff hands and bedrail; and two (6%) linked bed tables, bedrail and cardiac monitor. Conclusion: Colonized patients are responsible for repeated introduction of new S. aureus into the ICU, whereupon a proportion spread to hand-touch sites in (or near) the patient zone. This short-term reservoir for S. aureus imposes a colonization/infection risk for subsequent patients. More than half of ICU-acquired S. aureus infection originated from the patients' own flora, while staff hands and air were rarely implicated in onward transmission. Control of staphylococcal infection in the ICU is best served by patient screening, systematic cleaning of hand-touch surfaces and continued emphasis on hand hygiene.